Pengaruh Promosi Produk Dan Harga Terhadap Keputusan Pembelian Rumah Di Perumahan Alif Park Residence Depok - Mega Rahmawati; Aan Purnanama (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the Influence of Product Promotion and Price on Home Purchase Decisions at Alif Park Residence Depok. both partially and simultaneously. The method used in this study is a quantitative method. The sampling technique used is saturated sampling, which uses a sample of 92 respondents. The data analysis technique used is statistical analysis with validity test, reliability test, classical assumption test, simple linear test, multiple linear regression test, coefficient of determination, hypothesis t test and hypothesis f test. The results of the study of Product Promotion and Price on Home Purchase Decisions at Alif Park Residence Depok. Seen by the multiple linear regression equation Y = 1.787 + 0.378 X1 + 0.367 X2 This is evidenced by the results of the simultaneous hypothesis test obtained the value of f count> f table (156.021> 3.10) and strengthened by a significance value <0.05 (0.000 <0.05). The results of the coefficient determination test of the Product Promotion (X1) and Price (X2) variables gave an influence of 77.8%. On the Decision to Purchase a House at Alif Park Residence Depok. Thus, H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between the Influence of Product Promotion and Price on the Decision to Purchase a House at Alif Park Residence Depok.